A Comparison of Squatting Exercise on a Centrifuge and With Earth Gravity - Piotrowski, Timothy; Rittweger, Jörn; Zange, Jochen (Frontiers in Physiology, 2018)
Purpose: Long-duration space missions require countermeasures against the muscular wasting and cardiovascular deconditioning associated with microgravity. Replacing gravitational acceleration by means of centrifugation is a promising alternative as it challenges all physiological systems at once. The aim of this study is to examine the metabolic energy costs of squatting on a centrifuge in comparison with squatting in an upright standing posture under natural gravity. Methods: 24 subjects (11 male, 13 female) performed continuous squatting exercise for 9 min with increasing cadence (10, 12, and 15 squats min-1). This was done under three conditions: Upright under natural gravity and lying supine on a centrifuge at two radii (2.5 and 3.5 m) at 1 g of centrifugal acceleration at the subject’s average center of mass during the exercise. Results: Generally, subjects did not suffer from motion sickness. Exercise under natural gravity led to a higher Δ V’O2/body mass (7.1 ± 2.0, ml min-1 kg-1, mean ± SD) compared with exercise on the centrifuge (6.1 ± 1.6, ml min-1 kg-1, mean ± SD). Exercise efficiency was also reduced under natural 1 g at 28.2 ± 1.0% compared to 40.4 ± 1.5% on the centrifuge. As expected, oxygen consumption increased with increasing cadences. The Coriolis effect had a negligible impact as there was no significant difference in V’O2 between the two radii. However, during centrifugation and upward movement the right leg was more loaded than the leg left and vice versa during downward movement (centrifuge running clockwise looking down, so to the subjects’ right). Conclusion: The lower V’O2 on the centrifuge may be attributed to the unloading of trunk muscles while subjects were lying on the sled, which in the upright condition leaning against the sled were still working to stabilize the torso. Subjects tolerated high rotational rates combined with exercise very well.